The effects of undergarment composition worn beneath hockey protective equipment on high-intensity intermittent exercise - Noonan, B.; Stachelfeld, N. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to examine the impact of undergarment composition worn beneath ice hockey protective equipment on thermal homeostasis and power output, during a cycle ergometer exercise protocol designed to simulate the energy expenditure of a hockey game. We hypothesized that the layers of protective equipment would negate the potential thermoregulatory benefits from synthetic "wicking" undergarments but that subjects may feel more comfortable because of the inherent low moisture retention of these fabrics. Eight men (age, 25.4 ± 1.3 year) performed a repeated sprint test before and after a simulated game under typical hockey conditions (12°C; 82% relative humidity). This test was completed twice while wearing full protective equipment and either synthetic (SYN) or cotton (COT) full-length undergarments. During the simulated game, skin temperatures (34.22 ± 0.20°C vs. 34.46 ± 0.16°C) and core temperatures (37.50 ± 0.13°C vs. 37.59 ± 0.14°C) were similar between SYN and COT, respectively. There were also no significant differences found in sweat loss as a percent of body mass, heart rate, plasma lactate, sprint power, or ratings of perceived exertion between SYN and COT, respectively. The SYN retained less water than COT (140 ± 30 vs. 310 ± 30 g; p < 0.05); however, clothing and protective equipment weight gains as a whole were unaffected by the fabric worn (470 ± 110 vs. 590 ± 80 g) for SYN and COT, respectively. There were minimal differences in thermal sensation and undergarment wetness ratings during the simulated game. Thermoregulation and performance was driven more by properties of the layered protective equipment with minimal effects from undergarment composition.